2018
DOI: 10.1080/09546634.2018.1425358
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis treatment with adalimumab in clinical practice: long-term experience in a center for biological therapy in the Czech Republic

Abstract: Adalimumab is effective and safe in the long-term treatment of psoriatic patients in daily clinical practice. Once patients achieved PASI100, they tended to remain stable in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…A relatively high number of patients in this real-life study were bio-naïve (38.3%), even though risankizumab is the newest of a number of biologics registered for the treatment of psoriasis. This can be explained by the fact that physicians would prefer to initiate biologic therapy with a known drug demonstrating a high response rate, as it has been shown that patients achieving PASI 100 response have a higher chance of remaining stable during the treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively high number of patients in this real-life study were bio-naïve (38.3%), even though risankizumab is the newest of a number of biologics registered for the treatment of psoriasis. This can be explained by the fact that physicians would prefer to initiate biologic therapy with a known drug demonstrating a high response rate, as it has been shown that patients achieving PASI 100 response have a higher chance of remaining stable during the treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of biologic-naïve patients in our study was quite high (48.2%). This can be explained by the fact that physicians would prefer to initiate biologic therapy with a drug showing a high response rate [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Обсуждение. В клинической практике подтверждены эффективность и безопасность АДА у пациентов с псориазом и ПсА в долгосрочной перспективе [29][30][31]. Согласно результатам одноцентрового ретроспективного 9-летнего наблюдательного исследования с участием 316 пациентов (117 с псориазом и 199 с ПсА), частота ответа по индексам PASI75, PASI90, PASI100 к 12-й неделе терапии составила 65,1; 54,5 и 42,9%, а через год лечения -69,7; 62,2 и 44,4% соответственно, ответ на терапию сохранялся в течение всего периода наблюдения.…”
Section: нед подкожно после 3-й инъекции было достигнуто 50% улучшение по индексу Pasi уменьшение выраженности боли в суставах после 8-й unclassified